Illocutionary Act on Martin Luther King Jr. “I Have a Dream” Speech” - Aridewi, Ni Kadek Satya; Sedeng, I Nyoman; Parthama, Ngurah (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 30 No 2 (2023): September, 2023)
Abstract This research aimed at analyzing illocutionary acts found in Martin Luther King Jr. “I Have a Dream” Speech. This research implemented a descriptive qualitative method. The data source of this research was the speech of Martin Luther King Jr. uploaded on YouTube. The data were collected through note-taking techniques. The data were analyzed descriptively through data presentation and elaboration. The finding shows that there are five classifications of the illocutionary act, namely representative, directive, commissive, expressive, and declarative. Furthermore, the finding shows that there are twelve functions of the illocutionary acts found in the speech entitled “I Have a Dream” delivered by Martin Luther King Jr. They are claiming, reporting, complaining, commanding, requesting, advising, recommending, promising, expressing pleasure, expressing dislike, expressing sorrow, and naming.                            Keywords: illocutionary act, classification, function, speech   Abstrak Penelitian ini bertujuan untuk menganalisis tindak ilokusi yang terdapat dalam Pidato Martin Luther King Jr. “I Have a Dream”. Penelitian ini menggunakan metode deskriptif kualitatif. Sumber data penelitian ini adalah pidato Martin Luther King Jr yang diunggah di YouTube. Pengumpulan data dilakukan dengan teknik mencatat. Data dianalisis secara deskriptif melalui penyajian dan elaborasi data. Temuan menunjukkan bahwa ada lima klasifikasi tindak ilokusi, yaitu representatif, direktif, komisif, ekspresif, dan deklaratif. Selanjutnya, temuan menunjukkan bahwa terdapat dua belas fungsi tindak ilokusi yang ditemukan dalam pidato berjudul “I have a dream” yang disampaikan oleh Martin Luther King Jr. Mereka mengklaim, melaporkan, mengeluh, memerintah, meminta, menasihati, merekomendasikan, menjanjikan, mengekspresikan kesenangan, mengekspresikan ketidaksukaan, mengekspresikan kesedihan, dan penamaan. Kata kunci: tindak ilokusi, klasifikasi, fungsi, ucapan